Appréciation de la qualité technologique d’une collection de blé tendre (Triticum aestivum L.) cultivée en Algérie - LAMARA, Asma (Algerian Journal of Biosciences, 2021)
The wheat quality requirements are diverse and depend on the wheat species cultivated, the expected end-use product and the environment in which it is produced. In this study, 34 bread wheat varieties were evaluated for several physico-chemical and rheological parameters including thousand-kernel weight, grain moisture content, grain protein content, wet and dry gluten contents, sedimentation Zeleny test value and Hagberg falling number. It was observed that the extreme min and max values vary depending on the genotype evaluated and the test used, suggesting the difficulty of grouping all the desirable characteristics in the same genetic background. The results also show that there was a positive correlation of the Zeleny sedimentation value with grain moisture content, protein content, wet and dry gluten at phenotypic and genotypic levels. This test can be used to predict the wheat technological quality during the milling process. Furthermore, this study offers to breeders’ valuable information which, in future breeding programs, can be used to develop high yielding and adapted genotypes, and appreciated by the rheological and technological quality of their end-use product.